Answer :

Given:

[tex]y^{2}(2 y-5)-8 y+20[/tex]

To find:

The product of the expression.

Solution:

[tex]y^{2}(2 y-5)-8 y+20=y^{2}(2 y-5)+(-8 y+20)[/tex]

Take out -4 as a common factor in Last two terms.

                                [tex]=y^{2}(2 y-5)-4(2 y-5)[/tex]

Make sure the terms in both brackets must be same.

Take out common factor (2y - 5) from both terms.

                                [tex]=(2 y-5)(y^{2}-4)[/tex]

4 can be written as 2².

                                [tex]=(2 y-5)\left(y^{2}-2^2\right)[/tex]

Using the identity: [tex](a^2-b^2)=(a-b)(a+b)[/tex]

                                [tex]=(2 y-5)(y-2)(y+2)[/tex].

The product is [tex](2 y-5)(y-2)(y+2)[/tex].

Other Questions